(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Brain is a part of the organism’s complex structure that performs many functions, which are responsible for the main human abilities: to talk, to hear, to move, to see, etc. The brain consists of several areas that are not only directly connected with the different body systems, but also depend and may affect each other. Researchers and doctors are trying to summarize and visualize these relationships for an important purpose – to get the information about possible reactions of the body in case of various diseases, possibilities of recovery, risks, etc. important issues. Neurologists are looking for ways to "move" through the brain in virtual space for viewing the synapses between different areas. It might be useful to get a general idea of how brain regions are interrelated. The term "connectome", which is the complete structural description of the brain connections, or the map of connections, is used for the common perception of brain relationships. Connectome is a network of thousands of nerve fibres that transmits signals between the special regions responsible for functions such as vision, hearing, movement and memory, and combines these functions in a system that perceives, decides and acts as a whole. So, the relationships of brain neural regions can be represented as a graph with vertices corresponding to specific areas, but edges are links between these areas. This graph can be analysed using quantitative measures, like node degree, centrality, modularity etc. This article discusses the different network measures for the connections between brain's regions. The purpose is to determine the most important areas and the role of individual connections in the general functional brain model.